2011
DOI: 10.1016/j.molcel.2011.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of Mitochondrial Pyruvate Dehydrogenase Kinase 1 Is Important for Cancer Metabolism

Abstract: SUMMARY Many tumor cells rely on aerobic glycolysis instead of oxidative phosphorylation for their continued proliferation and survival. Myc and HIF-1 are believed to promote such a metabolic switch by, in part, upregulating gene expression of pyruvate dehydrogenase (PDH) kinase 1 (PDHK1), which phosphorylates and inactivates mitochondrial PDH and consequently pyruvate dehydrogenase complex (PDC). Here we report that tyrosine phosphorylation enhances PDHK1 kinase activity by promoting ATP and PDC binding. Func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
264
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 295 publications
(279 citation statements)
references
References 24 publications
13
264
1
1
Order By: Relevance
“…recently reported that tyrosine phosphorylation activates the upstream kinase of PDH, PDK1, to promote the Warburg effect in cancer cells and tumor growth (11). Our phospho-proteomics studies (11,12) and multiple proteomics-based studies performed by our collaborators at Cell Signaling Technology revealed that the upstream phosphatase of PDH, PDP1, is phosphorylated at a group of tyrosine residues in human cancer cells (Fig.…”
Section: Fgfr1 Inhibits Pdp1 Via Phosphorylation At Tyr-94 -Wementioning
confidence: 58%
See 3 more Smart Citations
“…recently reported that tyrosine phosphorylation activates the upstream kinase of PDH, PDK1, to promote the Warburg effect in cancer cells and tumor growth (11). Our phospho-proteomics studies (11,12) and multiple proteomics-based studies performed by our collaborators at Cell Signaling Technology revealed that the upstream phosphatase of PDH, PDP1, is phosphorylated at a group of tyrosine residues in human cancer cells (Fig.…”
Section: Fgfr1 Inhibits Pdp1 Via Phosphorylation At Tyr-94 -Wementioning
confidence: 58%
“…However, how oncogenic signals inhibit PDC to regulate cancer cell metabolism is not quite clear. We recently reported that oncogenic tyrosine kinases promote the Warburg effects in cancer and leukemia cells by attenuating mitochondria function via phosphorylation and activation of PDK1 (11). In addition, we found that acetylation at Lys-321 and Lys-202 inhibits PDHA1 and PDP1, respectively (12).…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…The dependence of the primed state on glycolysis likely confers a growth advantage that may be correlated to that seen in cancer cells through the Warburg effect. PDK1, 2, and 3 are all up-regulated in primed Elf1 cells (P < 0.01, P < 0.01, and P < 10 −5 , respectively), indicating that some of the mechanism of primed cell mitochondrial shutdown may be similar to that seen in the Warburg effect (15,16).…”
Section: Mitochondrial Metabolism As a Functional Marker Of Pluripotencymentioning
confidence: 86%